Perils and Promises of Pathogenic Protozoan Extracellular Vesicles - Olajide, Joshua Seun; Cai, Jianping (Frontiers in Cellular and Infection Microbiology, 2020)
Extracellular vesicles (EVs) are membranous structures formed during biological processes in living organisms. For protozoan parasites, secretion of EVs can occur directly from the parasite organellar compartments and through parasite-infected or antigen-stimulated host cells in response to in vitro and in vivo physiological stressors. These secreted EVs characteristically reflect the biochemical features of their parasitic origin and activating stimuli. Here, we review the species-specific morphology and integrity of parasitic protozoan EVs in concurrence with the origin, functions, and internalization process by recipient cells. The activating stimuli for the secretion of EVs in pathogenic protozoa are discoursed alongside their biomolecules and specific immune cell responses to protozoan parasite-derived EVs. We also present some insights on the intricate functions of EVs in the context of protozoan parasitism.